Predictors of Breastfeeding Initiation and Maintenance in an Integrated Healthcare Setting. (May 2017) - Henninger, Michelle L.; Irving, Stephanie A.; Kauffman, Tia L.; Kurosky, Samantha K.; Rompala, Kathryn; Thompson, Mark G.; Sokolow, Leslie Z.; Avalos, Lyndsay Ammon; Ball, Sarah W.; Shifflett, Pat; Naleway, Allison L.; ,
Background: The American Academy of Pediatrics recommends exclusive breastfeeding to age 6 months. Although breastfeeding rates in the United States have been increasing over time, further improvements are needed to meet Healthy People 2020 targets. Research aim: This study examined predictors of breastfeeding initiation and maintenance among a population of insured pregnant women. Methods: Participants were 1, 149 pregnant women enrolled in the Pregnancy and Influenza Project in two Kaiser Permanente regions in 2010-2011. Data were collected through interviews at enrollment and 1 month and 6 months postpartum and through participants' electronic medical records. Results: Nearly all (99%) women reported initiating breastfeeding. Rates of exclusive breastfeeding were 70% and 54% at 1 month and 6 months, respectively; an additional 22% and 23% of women reported supplementing breastfeeding with formula. Of the women who supplemented, the mean ( SD ) infant age at formula introduction was 53 (62) days. Of those who had stopped breastfeeding, the mean ( SD ) infant age at cessation was 85 (59) days. Higher maternal education level, better maternal self-rated health, prenatal folic acid use, absence of chronic medical conditions, and infant full-term birth were significantly associated with breastfeeding maintenance. Conclusion: Although rates of breastfeeding in this population were higher than national rates, a significant number of women stopped breastfeeding or introduced formula earlier than recommended. Two to 3 months postpartum may be a critical period warranting additional encouragement or intervention by healthcare providers. Mothers' education attainment, maternal health factors, and gestational age at delivery may predict likelihood of breastfeeding maintenance.